Interactive Math Path: Permainan Ular Tangga Berbasis Etnomatematika - Rani Puspita; Betty Kusumaningrum; Elfrida Yani; Kholifah Dinnisa; Krida Singgih Kuncoro; Annis Deshinta Ayuningtyas; Muhammad Irfan (UNION : Jurnal Ilmiah Pendidikan Matematika, 2022)
This research is a learning media development research that aims to produce an online snake and ladder learning media "Interactive Mathematics Path" on the Bangun Datar material using an ethnomathematical approach. The method used in this study is the Research and Development (R&D) method by adapting the 4D (four-D) development model. However, at the implementation stage, this research only reached the development stage by producing products that have been tested for validity and practicality. This research was conducted through four stages, namely (1) Defining, by analyzing the needs in learning, such as problem analysis, student analysis, concept analysis and analysis of learning objectives. (2) Design, by making prototypes (initial drafts of learning media) and research instruments. (3) Developing, by testing the product by validators and by students on a limited basis, then making improvements. The results of the validation of the learning media "Interactive Mathematics Path" are feasible with a slight revision and the percentage is 91.1%. The results of the limited trial show that the product of practice is used in learning with an average percentage of 88.4%.